169k views
4 votes
HELP ME PLS SOS

What is the value of x in the following equation? 3(x - 4) = 2x - (6 + x)​

HELP ME PLS SOS What is the value of x in the following equation? 3(x - 4) = 2x - (6 + x-example-1
User MatanRubin
by
6.9k points

1 Answer

5 votes

Answer:

x = 2

Explanation:

3(x - 4) = 2x - (6 + x)​ first get rid of parenthesis

3(x - 4) = 3x - 12 and

2x - (6 + x) = 2x - 6 - x

3x - 12 = 2x - 6 - x

3x - 12 = x - 6 export like terms to the same side

3x - x = 12 - 6

2x = 6 divide both sides by 2

x = 3

User Pons
by
5.7k points